The Witness Experience Inventory - Alarith Uhde; Lianara Dreyer; Marc Hassenzahl (Interacting with Computers, 2025)
Interactions with technology are part of social life, for example in cafés, trains, or parks. This social situatedness not only changes how users experience these interactions. It also influences the situated experiences for other co-located people (“witnesses”). However, despite a large body of research on user experiences, the relation between an interaction and witness experiences, and ways to design for them, remain underexplored. To address this gap, this paper introduces the “Witness Experience Inventory”, a research tool grounded in social-interpretivist theories, that offers a pragmatic approach to study how interactions with technology affect witness experiences. Based on an analysis of eight interactive technologies, we illustrate how the Witness Experience Inventory can inform the design of socially situated interactions with technology to avoid negative and create more positive witness experiences. We provide guidelines for applications of the Witness Experience Inventory in future research and its adaptable coding template. Both build on experiences from our own research, but give future researchers and practitioners the flexibility to adapt the tool to the social settings they study.
Keywords: 330; social situation; research method; qualitative; experience design; witness experience; social practice